(3GdeNJUQ aj TQM JdNjU GdeaJGM aj GdeYGfis - (3eSYhO Hf YeQ Hf YHO Gddg GdJaJGRGfj, SYO GdOjf , J (B793 (3g` s ((3eMeO Hf Ydi GdZRhGfi GdJhfSi s)
(3ChdgG (B:s
(3MeGeI LQYG MheI GdLfOd CSLYi aCfJ HeQCi ef SYGO heSeYi s
(3BNQgG (B:s
(3eTJedI Ydi dWa GdaGJMI , hefWhjI Ydi MSf GdNGJeI NJe Gddg dfG HGdMSfi hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hBdg CLeYjf Je GdcJGH hQHfG GdeMehO s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdHdGZIs